Visible-light-driven activation of peroxymonosulfate for accelerating ciprofloxacin degradation using CeO2/Co3O4 p-n heterojunction photocatalysts - Shen, Chun-Hui; Wen, Xiao-Ju; Fei, Zheng-Hao; Liu, Zong-Tang; Mu, Qi-Ming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Novel highly efficient visible-light-driven photocatalytic system Co3O4/CeO2/PMS is prepared.•87.8% of CIP could be removed within 50 min visible illumination.•The addition of PMS produced the synergetic effect in Co3O4/CeO2 photocatalytic system.•A plausible degradation pathway for CIP was proposed.•The in-depth mechanisms insight of charge separation. The development of simple and effective approaches for the synthesis of bimetallic oxide heterojunction photocatalyst which are used to activate peroxymonosulfate (PMS) under visible-light-driven is highly feasible but remains a great challenge. In this work, the Co3O4/CeO2 composite was prepared by a facile chemical reaction, followed by annealing in a muffle furnace and then applied to activate PMS for ciprofloxacin (CIP) degradation. Various characterizations confirmed the formation of p-n heterojunction between Co3O4 and CeO2. Meanwhile, the 5 wt% Co3O4/CeO2/PMS composite showed highest degradation rate of CIP (87.8%) under visible light irradiation. The obtained Co3O4/CeO2/PMS system still exhibited a good catalytic performance in presence of different anion. Besides, the active radical h+, OH, O2−, and SO4− are involved in CIP degradation. The excellent degradation performance can be interpreted as the synergistic effect between Co3O4/CeO2 heterojunction photocatalyst and PMS activation. Moreover, the energy band structure and valence band deviation of Co3O4/CeO2 p-n heterogeneous junction were confirmed. This work would give a reference for combining the photocatalyst and activation of PMS under visible light for further removal of pollutants.